ANALISIS IMPLEMENTASI KURIKULUM MERDEKA BELAJAR DALAM MENINGKATKAN PEMAHAMAN SISWA - AZIZ NURI SATRIYAWAN NURI (EBTIDA': Jurnal Pendidikan Dasar Islam, 2025)
The curriculum has undergone changes, one of which is the implementation of the Merdeka Belajar (Freedom of Learning) curriculum, which is still considered new and is still in the gradual implementation stage. Nevertheless, many schools have implemented this curriculum with a focus on learning that provides freedom according to the needs and characteristics of students. Therefore, the purpose of this study is to analyze the Merdeka Belajar curriculum in improving the understanding of students at Muhammadiyah 1 Karangjati Elementary School. The research method applied was a qualitative method with a field research type. Meanwhile, data collection techniques used interviews, observation, and documentation. The researcher used documentation techniques related to the values ​​of Social Sciences and Pancasila Education, both during the implementation of the 2013 curriculum and after the implementation of the Merdeka Belajar curriculum. In addition, this approach also involved observation and interviews with respondents as additional methods to obtain more in-depth data. The respondents who became the subjects of the study were 10 respondents, including 8 students and 2 teachers. The analytical method used in the study was descriptive. The collected data was then analyzed in depth, resulting in research findings showing that the implementation of the independent learning curriculum in the subjects of Science and Pancasila Education at Muhammadiyah 1 Karangjati Elementary School, Ngawi Regency, had shown an increase of 10 points, as evidenced by the increase in the average student learning outcomes.